Differences in Sun Protection Behaviors Between Rural and Urban Communities in Texas. Issue 2 (4th March 2019) - Cunningham, Sonia A.; Yu, Robert; Shete, Sanjay
Abstract: Purpose: The increasing incidence of skin cancer is a global health issue. In order to identify at‐risk populations in Texas, we compared sun protection behaviors and sunburn history across rural and urban counties. Methods: An online health screening survey collected data from a nonprobability sample of Texas residents in 2018. Data were weighted by sex, age, race, and ethnicity. Multinomial multivariable logistic regression identified key factors associated with sun protection behaviors and sunscreen use. Weighted Pearson's χ 2 test identified differences between urban and rural respondents in strength of sunscreen used and sunburn history. Findings: Rural residents in Texas were less likely to seek shade (OR = 0.58; P = .004) and less likely to use sunscreen lotion (OR = 0.65; P = .013) compared to their urban counterparts. Sunscreen use was also lower among current versus never smokers (OR = 0.67; P = .034) but higher in those with personal versus no cancer history (OR = 2.14; P = .004). Although rural versus urban residents were more likely to use higher SPF sunscreen ( P < .002), they had more blistering sunburns over the course of their life ( P < .001) and these injuries were more likely to occur at an earlier age, between 5 and 14 years old ( P < .001). Conclusions: Increased attention to sun protective behaviors among rural communities in Texas is vital to help reduce the high prevalence of sunburn injury and incidence of skin cancer.